Pressure-induced valence fluctuation in CsEuF3: From divalent Eu valence to trivalent Eu valence state - Nakagawa, Takeshi; Vrankić, Martina; Menelaou, Melita; Sereika, Raimundas; Wang, Dong; Zhang, Jianbo; Ishii, Hirofumi; Hiraoka, Nozomu; Ding, Yang (My University, 2023)
The ternary rare-earth metal fluoride CsEuF3 adopts an ideal cubic perovskite structure [ABX3] under ambient conditions. The B-cation site is occupied by the rare-earth Eu ion and EuF6 octahedra are formed. In the present study, magnetic susceptibility and synchrotron X-ray absorption spectroscopy (XAS) analysis at the Eu-L3 edge confirmed that Eu is in a divalent oxidation state under ambient conditions. Temperature-dependent magnetic susceptibility data revealed that the average Eu valence increased below 20 K due to a partial transition from the Eu2+ state to the Eu3+ state, thereby resulting in a mixed valence state with an average valence of +2.23. Direct evidence for valence fluctuation by the Eu ions in CsEuF3 was obtained using the high pressure high energy resolution fluorescence detection-XAS technique, where continuous changes in valence were observed from 2.15+ at ambient pressure up to 2.5+ at 10.5 GPa. These findings indicate the possibility of discovering interesting physical properties associated with valence instabilities by rare-earth metals in similar systems.
Keywords: Perovskites; Rare-earth elements; Valence fluctuation; Synchrotron X-ray absorption spectroscopy; High pressure